The Effect of the Application of Circuit Training Exercises in Increasing Freestyle Swimming Leg Speed - Syamsul Anwar; Dinar Dinangsit; Rizal Ahmad Fauzi (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
This study aims to determine the effect of circuit training on freestyle swimming leg speed in athletes aged 8–12 years. Foot speed is one of the important factors that affect swimming performance, so effective training methods are needed to improve it. This study used an experimental method with a pretest-posttest control group design. The study sample amounted to 30 athletes who were divided into experimental groups and control groups. The experimental group was given treatment in the form of circuit training exercises, while the control group underwent routine exercises. Data collection was carried out using a freestyle leg speed test of 25 meters measured in units of time (seconds). The results showed that both groups experienced improvement, but the improvement in the experimental group was higher than in the control group. The average time in the experimental group decreased from 39.53 seconds to 32.33 seconds, while in the control group decreased from 41.00 seconds to 39.47 seconds. The results of statistical analysis showed a significant difference between the two groups. These findings show that circuit training is more effective than regular exercise in increasing freestyle leg speed. The novelty of this study lies in the application of circuit training as a structured ground training method to increase foot speed in early age athletes. This study provides empirical evidence on the effectiveness of dryland circuit training in enhancing lower-limb propulsion performance in young swimmers.